Mothers-in-law and son preference in India - Robitaille, Marie-Claire; Chatterjee, Ishita (Sameeksha Trust, 2017)
In India, the mothers-in-law are often portrayed as the most powerful entity in the household in Indian popular culture and media. Similarly, in the literature, the influence of the Indian mothers-in-law is often taken for granted. However, most of the empirical evidence relies on qualitative data or on small samples. Looking at stated son preference and using the third nationally representative National Family and Health Survey dataset, we show that mothers-in-law do indeed have an influence on their daughter-in-law, everything else constant. Given the stronger son preference among mothers-in-law, this contributes to the high imbalance in the male to female sex-ratio observed among children in India.